Understanding the digital divide: A literature survey and ways forward - Chalita Srinuan; Erik Bohlin (International Telecommunications Society (ITS), 2011)
The term digital divide was introduced in the mid-1990s and defined as the gap separating those who have access to new forms of information technology from those who do not. The digital divide remains an important public policy debate that encompasses social, economic and political issues. This paper presents a literature review and classification scheme for digital divide research. The review covers journal articles published between 2001 and 2010 in three types of journals: (1) Information technology & information systems, (2) Economics and business & management and (3) Social science. A classification of digital divide literature and a comprehensive list of references are provided. The results show that the digital divide is a multifaceted phenomenon, due to the many dimensions of determinant factors. Recent studies have included socio-economic, institutional and physiological factors in order to gain a greater understanding of the digital divide. Among other findings, they show that technological determinism is not sufficient to explain the emergence of the digital divide. Moreover, several types of technologies were investigated, both from empirical and conceptual standpoints. The Internet is the most commonly studied technology. The divide in access and usage are discussed at the global, social and democratic levels by employing a quantitative method, either a survey or data analysis, as the main method. However, there is less discussion in developing countries and at the level of the organization (i.e. SMEs, the private sector and the public sector). The qualitative research method could be seen as a complementary method to fill the gap in the current research. The choice of policies which have been recommended to the policy maker and national regulatory agency (NRA) are also presented and discussed at the end of this paper. Several initiatives made at the country and regional levels and by international organizations have also attempted to create a combined policy. This may suggest that the combined policy is the current trend among digital divide policies. Therefore, there is a need for future research to examine these determinants through the context of global, social and democratic divides. The results would provide some insight into how diverse people in different areas adopt ICTs.
Keywords: 330; Digital divide; Literature review; Future research